Analysis of the relationship between exchange rate fluctuations and per capita income: A statistical study - Lamiaa Abdul-Jabbar Dawod; Mustafa Abduljabbar Dawood; Waleed Ahmed Hassen Al-Nuaami (International Journal of Computational and Experimental Science and Engineering, 2025)
To study this relationship, an econometric study will be conducted, using statistical techniques to examine relevant economic data and develop forecasting models. The primary objective is to assess how fluctuations in exchange rates affect per capita income in a given country or group of countries over a specified period of time. Econometric techniques, including regression analysis, will be used to identify patterns and associations between the two variables.